Pemanfaatan Model Simulasi Berbasis Teknologi Informasi dan Komunikasi Terhadap Minat Belajar Siswa pada Mata Pelajaran Qur’an Hadits - Aisyah, Siti (Afkaruna: International Journal of Islamic Studies (AIJIS), 2024)
Theuse of classical methods or lectures is considered by teachers to be the most frequently used method of managing classes and being able to pursue material targets that must be completed. Using the lecture method the role of the teacher in the classroom is very dominant, the teacher as the subject of the informer and the teacher is the center of attention and the teacher speaks more while the students listen or record the things conveyed by the teacher. . Against the backdrop of this problem, this study aims to reveal the use of information and communication technology-based simulation models for learning interests in elementary school students. This type of research is descriptive qualitative with a case study method. Data were collected through observation and interviews as well as sources relevant to the study. Furthermore, the data that has been collected is analyzed by reducing the data, presenting the data and drawing conclusions. The results of this study show that utilizing a simulation model based on information and communication technology can increase students' interest in learning. With results that can be seen in each indicator of student interest in learning include: students are happy in learning, have an interest in learning, pay attention to the material presented and involvement in simulating the practice of prayer movements.